Penerapan Penerapan Teknologi Berbasis AI dalam Penilaian Keterampilan Praktis Siswa: Studi Eksperimen di MI NU Manbaul Huda: Penerapan Teknologi Berbasis AI dalam Penilaian Keterampilan Praktis Siswa: Studi Eksperimen di MI NU Manbaul Huda - Supriyanto, supriyanto; Naila Fitriyana, Naila Fitriyana (JCI Publisher, 2025)
This study explores the application of AI-based technology in assessing students' practical skills through an experimental approach at MI NU Manbaul Huda. The background of this research stems from the challenges of traditional assessment methods, which are often subjective, time-consuming, and inconsistent. The study aims to evaluate the effectiveness of an AI-based assessment system in improving the accuracy and efficiency of practical skill evaluation. The methodology involves a quasi-experimental design, comparing an experimental group using the AI system with a control group using traditional methods. Data were collected through observation, questionnaires, and interviews with teachers and students. The results show that the AI system achieved an accuracy rate of 89%, significantly higher than the traditional method's 75%. Additionally, 85% of teachers and 90% of students expressed positive perceptions of the AI system. The study concludes that AI-based technology has the potential to transform practical skill assessment by providing objective, real-time feedback. This research contributes to the field of educational technology by demonstrating the feasibility and benefits of AI in primary education, particularly in Islamic-based schools. Recommendations include teacher training and infrastructure improvements to support broader implementation.Keywords: AI-based assessment, practical skills, primary education, Islamic schools, educational technology.